Military gadgets : how advanced technology is transforming today's battlefield-- and tomorrow's - Evans, Nicholas D. (Financial Times Prentice Hall, 2004)
"Nicholas D. Evans offers easy-to-read descriptions of more than 75 technologies, and how they are used, all set within the broader context of military transformation. Evans covers the entire spectrum of military technologies from the present-day "heavy" forces comprised of aircraft, tanks, ships, and submarines, to the future-state light and agile forces exemplified by transformational programs such as the Army's Objective Force and the Navy's Sea Power 21." "Military Gadgets covers equipment used in every service of the military and created by an extraordinary range of top military contractors and innovators. Whether you're a military or defense professional, researcher, policymaker, or citizen, this is your complete guide to the future of warfare."--Jacket